DRUNKENNESS AS A REASON FOR TERMINATING EMPLOYMENT RELATIONSHIP AND STATE SERVICE EMPLOYMENT RELATIONSHIP - Bite, Kitija (Administrative and Criminal Justice, 2016)
The author in the article researches alcohol as one of the reasons to terminate public service employment relationships at the State Police and employment relationships. The legislation provides different regulatory approach to alcohol intoxication as a reason for terminating the employment relationships and the legal application of this reason. In practice, detecting of alcohol intoxication and denunciation of employment relationship or retiring from the public service is problematic. The government regulations in Latvia define the inspection procedure of the influence of alcohol, narcotic, psychotropic or toxic substance, however, there is no legislative act defining the term ‘alcohol intoxication’, while it is essential in employment relationships. There are several issues that emerge from the case-law: firstly, the employer must legally differentiate alcohol intoxication from alcohol influence in order to be able to terminate the employment; secondly, the employer must legally/judicially detect and record the presence of alcohol. The author suggests to define the state of ‘alcohol intoxication’ as well as make alterations in the Labour Law giving the liberty to the employer to terminate the employment relationship in case of alcohol influence. A Chief of Public Institution should be appointed to develop An Internal Regulations Act in order to detect alcohol intoxication or influence. Such alterations in Law would allow the employer to apply disciplinary penalty or denunciation in the cases of alcohol intoxication, and would clearly define the inspection procedure for the employees upon suspicion of being present at work or public service under the influence of alcohol.